Application of cancer‐associated glycoforms and glycan‐binding probes to an in vitro diagnostic multivariate index assay for precise diagnoses of cancer. Issue 24 (11th May 2016) - Kang, Jeong Gu; Ko, Jeong‐Heon; Kim, Yong‐Sam
Abstract : Personalized medicine has emerged as a widely accepted trend in medicine for the efficacious and safe treatment of various diseases. It covers every medical treatment tailored according to various properties of individuals. Cancer‐associated glycosylation mirrors cancer states more precisely, and this "sweet side of cancer" is thus intended to spur the development of an advanced in vitro diagnostic system. The changes of glyco‐codes are often subtle and thus not easy to trace, thereby making it difficult to discriminate changes from various compounding factors. Special glycan‐binding probes, often lectins, can be paired with aglycosylated antibodies to enable quantitative and qualitative measurements of glycoforms. With the in vitro diagnosis multivariate index assay (IVDMIA) considered to be capable of yielding patient‐specific results, the combinatorial use of multiple glycoproteins may be a good modality to ensure disease‐specific, personalized diagnoses.